SEED CAPITAL FINANCING VALUATION OF M-HEALTH SERVICE STARTUP CASE STUDY: CAGEUR.IN - Rachmat, Eraulia Nadinda; Soekarno, Subiakto (Journal of Business and Management, 2017)
Abstractâ€”Mobile Health or M-Health has becoming more popular in the effort of supporting healthcare services through mobile apps. In Indonesia, the government tries to reach a Universal Health Coverage (UHC) through its National Insurance program called JKN (Jaminan Kesehatan Nasional). As the growing members of JKN to reach the UHC, the number of patients who are going to go to the clinics will also increased. Sick patients will make clinics business spend higher cost that eventually will make them suffer from heavy losses. Cageur.in company is a startup founded in 2016 that tries to help reducing the cost of the clinics by reducing the number of sick patients through its digital platform for clinics. However they are still in the seed stage without any revenues and require some capital to finance its operational. Therefore they need to find a suitable source of financing to support their business. The purposes of this research are to find Cageur.in enterprise value in order to prepare Cageur.in to seek for seed capital financing. We will apply several valuation methods which are recommended for valuating the seed stage startups. From the assessment of five valuation methods the results show Berkus method generates USD 1,400,000 valuation, Scorecard method shows USD 900,999, Risk Factor Summation method shows USD 1,320,956, DCF shows a USD USD4,897,766 valuation and Venture capital method shows a USD USD 4,398,765Â  valuation. For a seed stage startup like Cageur.in, Berkus, Scorecard and Risk Factor Summation method are more preferable than the two following methods which are DCF and VC method. This is due to the lack of financial records that makes finding the right input factors used the later methods such as growth rates, cost of capital and other underlying financial assumptions for forecasting its future financial projections is difficult.Keyword: Financing, Healthcare, Seed Stage, Startup, Startup Valuation